Institutional barriers to an intermodal integrated public transport system in the City of Cape Town - Jacobs, Ross (School of Architecture, Planning and Geomatics, 2023)
Across the world, public transport is acknowledged as a crucial feature of any major city. In many countries, an efficient public transport system has been achieved by establishing an intermodal integrated transport system. In other words, integrating public transport modes for better coordination and efficiency. However, public transport in the City of Cape Town is inefficient and lacks coordination. Thus, the City of Cape Town experiences high volumes of congestion as a result of increased private car use. Over the years, the City has produced many plans and policies in line with the national and provincial legislation to create an intermodal integrated transport system. However, this transport system has yet to materialise. Therefore, this study aims to investigate the institutional barriers that impact the extent to which an urban public transport system can be integrated. The aim was achieved through collecting data from several interviews with public and private professionals involved with transport in the City of Cape Town. The interview data was analysed in relation to literature and policy documents. The results of this study show that fragmentation of the ownership of public transport modes is one of the most significant and overarching barriers to integration. Solving this fragmenting has proved difficult due to continuous institutional restructuring at local and national government levels, which results in the draining way of leadership and capacity. Another significant barrier to integration is the unique difficulties of integrating the paratransit (minibus taxi) sector as it is fragmented, operates at an enormous scale, experiences resistance to integration and is characterised by instability as a result of violence. Political tensions between opposing political parties at different levels of government and within the City of Cape Town also acted as barriers since they resulted in instability and a lack of coordination. Funding constraints for various aspects of integration are also a barrier. Finally, one of the most profound barriers was that although there are plenty of policies for integration throughout the three spheres of government, the findings suggest a lack of common vision and political will behind policies hinders implementation. This is coupled with siloed planning and old mindsets. Some also argue that many overarching policy visions for integration may be entirely incorrect in the first place.